Penilaian Indeks Kinerja Sistem Irigasi (Studi Kasus Daerah Irigasi Cirompang Kabupaten Garut Jawa Barat) - Agus Sidharta; Bambang Priyambodo (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Irrigation is an effort to provide, regulate and distribute irrigation water. The Cirompang Irrigation Area is located in Bungbulang District, Garut Regency, West Java Province, with a functional area of 847 Ha, covering the service area of 4 (four) villages, namely Cihikeu Village, Bungbulang Village, Margalaksana Village and Hanjuang Village, Bungbulang District. The location of the Cirompang Irrigation Area Weir is in the village of Cintarasa, Samarang sub-district. The availability of water in the upstream, downstream and main network areas during the planting season I to planting season III is felt to be sufficient but in the middle areas the availability of water is reduced or it can be said to be non-existent due to reduced water potential and there are damaged irrigation networks and accumulation of sedimentation which results in obstruction of water flow. The Cirompang secondary canal experienced moderate to moderate damage, there was accumulation of mud or sedimentation which affected the flow of water and besides that there was also a lack of personal O&M officers in the field such as irrigation officers, weir operation officers, water gate officers and workers who have so far relied on participation. water user farmers (P3A/GP3A). The research method was carried out by direct observation in the field, interviews and secondary data analysis. Calculation of the real need for operation and maintenance is needed to determine the O&M funding and priority recommendations proposed to increase the value of irrigation system performance appraisal (IKSI). The results of the IKSI assessment for the Cirompang irrigation area, the combined index value is in the bad criteria, namely with a weight value of 48.14%, meaning that the irrigation network requires rehabilitation of the irrigation system and needs immediate treatment. 117,626,150.00 In addition, O&M financing in Cirompang for the last 3 years is still far from ideal conditions, namely an average of only 10% of AKNOP. Efforts to increase the water discharge, it is suggested for the Public Works and Spatial Planning Office of Garut Regency is to increase the budget allocation, empower the participation of water-using farmers and rehabilitate irrigation networks.